2017
DOI: 10.1159/000486153
|View full text |Cite
|
Sign up to set email alerts
|

CpG-Oligodeoxynucleotides Improved Irradiation-Induced Injuries by G-CSF and IL-6 Up-Regulation

Abstract: Background/Aims: This study investigated the radioprotective properties of three classes of CpG-oligodeoxynucleotides (CpG-ODNs) and the underlying mechanisms. Methods: Mice irradiated at different doses(7Gy or 9Gy) were treated with or without ODNs(50μg via intraperitoneal injection). Assays were performed to determine survival rate and the number of white blood cell in peripheral blood. The levels of granulocyte-colony stimulating factor(G-CSF), interleukin 6(IL-6) and interferon-α (IFN-α) were measured usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that KSK CpG-ODN (K-CpG) effectively protects mice from radiation-induced lung injury by modulating innate immune responses [ 7 ]. Furthermore, research has indicated that all three types of ODNs can protect mice from radiation-induced damage, with B-grade ODNs demonstrating the most effective characteristics in radioprotection, possibly achieved through upregulating the expression of G-CSF and IL-6 [ 8 ]. In comparison to these studies, our findings suggest that CpG-ODNs may alleviate renal injury caused by cervical cancer radiotherapy (RKI) by inhibiting the activation of the PARP1/XRCC1 signaling axis, thus suppressing DNA damage and oxidative stress responses in renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that KSK CpG-ODN (K-CpG) effectively protects mice from radiation-induced lung injury by modulating innate immune responses [ 7 ]. Furthermore, research has indicated that all three types of ODNs can protect mice from radiation-induced damage, with B-grade ODNs demonstrating the most effective characteristics in radioprotection, possibly achieved through upregulating the expression of G-CSF and IL-6 [ 8 ]. In comparison to these studies, our findings suggest that CpG-ODNs may alleviate renal injury caused by cervical cancer radiotherapy (RKI) by inhibiting the activation of the PARP1/XRCC1 signaling axis, thus suppressing DNA damage and oxidative stress responses in renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Each mouse was intraperitoneally injected with 50 μg of CpG-ODNs or saline solution, five times per week, followed by every fourth session. The mice were exposed to X-ray irradiation, five times per week, for a total of 4 weeks [ 7 , 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, TLR9 recognizes unmethylated CpG oligodeoxynucleotides and promotes IL-6 secretion and consequent B cell activation (158)(159)(160)(161)(162)(163)(164)(165)(166)(167)(168). It has been demonstrated that enhancement of TLR9 receptors augment activity of antigen-presenting cells in neonates (93, 102, 169).…”
Section: Toll-like Receptors Agonistsmentioning
confidence: 99%
“…Since Burdelya et al reported that toll-like receptor 5 agonists had radioprotective effects in mice as well as monkeys (13), a large number of studies on TLR agonists as a response against radiation injury have been carried out. Over the past 10 years, our group has been studying the role of TLR ligands in radioprotective effects and has demonstrated that TLR2, TLR4, TLR5, and TLR9 agonists inhibit radiation-induced apoptosis and increase cell survival (14)(15)(16)(17). Among them, lipopolysaccharide (LPS), a potent TLR4 agonist, dramatically improves the survival of mice exposed to fatal radiation doses.…”
Section: Introductionmentioning
confidence: 99%